111In-Pentetreotide (OctreoScan) scintigraphy in the staging of small-cell lung cancer: its accuracy and prognostic significance. Issue 2 (February 2015) - Genestreti, Giovenzio; Bongiovanni, Alberto; Burgio, Marco Angelo; Burgio, Salvatore Luca; Musto, Alessandra; Rossi, Alice; Monti, Manuela; Scarpi, Emanuela; Ulivi, Paola; Bravaccini, Sara; Dubini, Alessandra; Matteucci, Federica; et al.
Abstract : Background: Small-cell lung cancer (SCLC) may express somatostatin transmembrane receptors (SSTRs) in 50–75% of cases. We evaluated the accuracy and prognostic significance of somatostatin receptor scintigraphy (SSRS) in staging compared with conventional radiological procedures. Patients and methods: Newly diagnosed SCLC patients underwent scintigraphy with the radiolabeled somatostatin analog indium-111 ( 111 In)-pentetreotide (OctreoScan). Histological data were available for 20 (38%) patients for immunohistochemical analysis of SSTR-2 expression. Results: From May 2007 to December 2011 we analyzed 52 SCLC patients. In comparison with standard radiologic staging, the sensitivity and specificity of SSRS were 63 and 100% for primary pulmonary tumor (T), 51 and 100% for mediastinal lymph node (N), and 23 and 91% for metastatic disease (M), respectively. The overall SSRS accuracy was 65% for T, 62% for N, and 52% for M. Patients with positive SSRS achieved a disease control rate of 97 versus 84% in those with negative exam results; median progression-free survival was 9.5 months versus 11.0 and median overall survival was 15.3 versus 14.5 months for patients with positive SSRS versus those with a negative result. Notably, seven (78%) patients with a positive quantitative analysis for SSTR-2 had a positive SSRS; at semiquantitative analysis this correlation was found in eight (73%) patients. Conclusion: SSRS has a lower accuracy in comparison with standard radiological staging in SCLC. However, patients with a positive SSRS given standard treatments showed better disease control compared with those with a negative SSRS, but similar progression-free survival and overall survival.